Effects of Heating- or Caustic-Digested Starch on its Flocculation on Hematite. (2nd January 2016) - Tang, M.; Wen, S.; Liu, D.
ABSTRACT: Selective flocculation of heating or caustic-digested starch on hematite is well practical. What happens to the starch from alkali-digestion at room temperature or heating-treatment, however, may not be fully understood. An attempt to identifying possible effects of heating- or caustic-digested starch on its adsorption characteristics on fine hematite was made through a series of tests, like adsorption test, micro-flotation test, turbidities test, Fourier transform infrared spectroscopic analysis (FTIR), and Aggregation/dispersion measurement as well. All results from these tests pointed out that those traditional digestion methods have a significant influence on adsorption density of starch on mineral surfaces, as well as its adsorption mechanisms. Since a certain amount of carboxyl groups on the starch remnants resulted from heating- or caustic-digestion probably attributes to the acid/base interaction between the starch and hematite. And much more amounts of carboxyl groups seem to be harvested from the starch digested with sodium/potassium hydroxide at higher concentrations. But the homogeneous and transparent starch gel from alkali-digestion at a concentration of more than 2% at room temperature, consisting of a great many short-chain remnants, may probably weaken its flocculating capacity on hematite and lead to performing a potentially dispersing role instead. It is also worthy to notice that the starch gel from a combination of caustic-digestion at a 1.5 weight ratio of sodium hydroxide to starch and heating-treatment at the temperature of 100°C reached an adsorption density of almost 12 mg/g hematite, compared with 9.0 mg/g from caustic-digested starch at same concentration or 6.2 mg/g from heating-treated starch in boiling water only.